Rural Women Farmers' Participation In Maize Value Chain And Socio-Economic Empowerment In South-West Nigeria - Awoyemi, Adeseye Oluwasikemi; Adesiji, Gbolagade Benjamin; Omotesho, Kemi Funmilayo (Jambura Agribusiness Journal, 2023)
In recent times, there has been increased participation of women in agricultural value chain, but their empowerment status is poor. Thus, evidence-based data revealing the socio-economic status of rural women participating in maize value chain is important to further strengthen women's participation in the agricultural value chain sector. The study aimed at examining participation in maize value chain and socio-economic empowerment among women in South-west Nigeria. A three-stage sampling procedure was employed in the selection of respondents for the study. The first stage involved proportionate random sampling of three states in South-west, Nigeria. Second stage involved the generation of a sample frame from the various associations of rural women farmers in MVC in the Agricultural Development Programme zones. Last stage, 20% of the total of rural women farmers involved in MVC was selected to give a sample size of 539 respondents. Data were collected through interviewer-administered questionnaire and analyzed using both descriptive and inferential statistics. The findings from the study were that the participation mean score of the respondents in marketing and processing were high (71.2%, 73.1%) respectively, the mean participation score in MVC was 67%; respondents' percentage mean score based on socio-economic empowerment status after participation in MVC was high (60%). Major constraints to participation in MVC activities were high cost of transportation to market (xÌ„=1.27) ranked 1st and inadequacy of extension service delivery (xÌ„=1.22) ranked 2nd; and participation in MVC activities had positive and significant relationship with the socio-economic empowerment status of the respondents (r=0.380; p=0.000). The study concluded that the level of rural women farmers' participation in MVC activities was high and impacted their socio-economic status positively. The study recommended that agricultural extension agency should focus on empowering the rural women by providing extension services needed for market linkage and bulk transportation of produce to target markets.